The relationship between physical infrastructure and the perception of students’ performance in community Islamic schools in Perak, Malaysia - Mohamed Osman, Mariana; Bachok, Syahriah; Rabe, Noor Suzilawati; Jaafar, Samsuddin; Ahmad Thani, Siti Nur 'Alia (American Scientific Publishers, 2017)
Malaysia has a (64%) majority Muslim population. It is imperative that Islamic schools be provided because vernacular schools have limited curriculum capacity to accommodate the Islamic teachings on daily basis. Hence, examining the provision of Islamic schools, their physical conditions and educational facilities, including laboratories and libraries is essential to establish the existence and severity of issues and problems facing these schools as well as to ensure their relevance and sustainability. Data was collected primarily through questionnaire surveys on parents’ and teachers’ perception of the students’ performance and also secondarily from analysis of contents of published documents and site inventories. Inadequacy of such inventoried facilities was one of the major findings. Apparently, some levels of financial and monetary assistance were indeed necessary to improve the physical conditions of schools, as well as guaranteeing the schools longevity. In essence, the findings conform to literature regarding the propagation of students’ educational performance being indeed influenced by the state of both physical and infrastructure provision. It is hence, suggested that financial aids targeting on the renovation and upgrading of these provision be promptly initiated.